Industrial training report: Permodalan Nasional Berhad / Syazaliana Abdul Hamidi - Abdul Hamidi, Syazaliana (Faculty of Business and Management, 2025)
In the name of Allah, the Most Gracious, the Most Merciful, I extend my profound gratitude to Allah (SWT), the Most Beneficent and Merciful, for His continuous blessings and guidance throughout my industrial training experience. This invaluable opportunity allowed me to gain practical knowledge, develop professionally, and enhance my skills. I wish to express my sincere appreciation to my supervisor, Mr. Nazrul Azuan Bin Nazri, for his exceptional guidance, support, and mentorship during my internship at Amanah Saham Nasional Berhad (ASNB). His dedication to fostering a supportive learning environment and sharing his expertise was pivotal to my personal and professional growth. I also acknowledge the contributions of the entire ASNB Seremban team, whose cooperation, shared knowledge, and collaborative spirit significantly enriched my learning experience. Their assistance and encouragement created an environment conducive to my development, for which I am truly grateful. Additionally, I am deeply indebted to my parents for their unwavering support, encouragement, and sacrifices throughout my academic journey. Their steadfast belief in my abilities has been instrumental in my accomplishments. Lastly, I extend my heartfelt thanks and prayers, Jazakallahu Khairan (May Allah reward you with goodness), to everyone who has contributed to my growth and success in any capacity.